Pengaruh Kinerja Keuangan, Tingkat Inflasi dan PDB Terhadap Harga Saham Perusahaan F&B - Suryanto, Suryanto; Kesuma, I Ketut Wijaya (E-Jurnal Manajemen, 2013)
F&B sector is a sector with stocks that are defensive. Since both in a state of crisis and growing communities will still need the product. Supported also by growing too JCI since 2002 until today making a stock investment is very promising. Thus came the idea to analyze the effect of financial performance, the level of inflation and GDP growth rate of the stock price in the sector of F&B period 2007-2011. The sampling method used purposive sampling and sample obtained 11 companies. The data used are secondary data in the form of annual analyzed using multiple linear regression. At ? = 5percent and the value of R square = 0,976 obtained simultaneously all the variables studied had a significant effect on stock prices, partially variable PER and EPS has positive and significant effect on stock prices, other variables such as : ROE, inflation rate and GDP growth rate has no significant effect on stock price.   Keywords: stock price, financial performance, the level of inflation, and GDP growth rate